Analysis of Soil Quality Index type of land use on dry land in Blang Bintang sub-district, Aceh Besar Regency - Umar H A; Endiyani Endiyani; Sri Agustina; Irhami Irhami; Chairil Anwar; Irmayanti Irmayanti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
This study aimed at examining the analysis of the soil quality index of dry land use on dry land in Blang Bintang District, Aceh Besar District. This research was conducted using a descriptive method based on the results of surveys and field observations as well as laboratory analysis. General biophysical conditions of the area and physical and chemical characteristics of the soil obtained from observations and indicators of soil quality through soil analysis in the laboratory. Soil sampling points were determined using the purposive sampling method, namely the points that have been determined on selected dry land in Blang Bintang District, Regency of Aceh Besar. The moderate soil quality index in the upland land use type is one of the reasons for the sampling of the Inceptisol soil type in the Blang Bintang sub-district, which has less fertile soil characteristics. Upland land use is the percentage of sand (57%) which is greater than the percentage of dust (36%) and clay (6%). This can be seen in the low content of C-organic (1.19), H2O, K-dd, P-available and N-total and high volume weight (1.34).